2008
DOI: 10.1158/0008-5472.can-07-6168
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Signaling and Aryl Hydrocarbon Receptor Mediate Synergistic Induction of Interleukin 6 in MCF-7 Cells

Abstract: The pleiotropic cytokine interleukin 6 (IL-6) is involved in immune cell homeostasis. Additionally, IL-6 expression and signaling in tumor cells have been shown to elicit both protumor and antitumor properties. There is a plethora of mechanistic knowledge regarding how IL-6 signal transduction translates to biological responses. However, there is little understanding as to what factors control IL-6 expression within a tumor cell environment. The studies presented herein show that, in MCF-7 breast and ECC-1 end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 48 publications
(55 reference statements)
6
75
1
Order By: Relevance
“…Exogenous AHR agonists appear to have dual effects on inflammatory signaling. On the one hand, TCDD exposure can induce inflammatory responses as exemplified by: (a) the synergistic induction of IL-6 expression caused by interleukin-1ÎČ and TCDD co-treatment via an AHR-dependent and DRE-mediated mechanism (Hollingshead et al 2008); and (b) induction of Socs3 expression by TCDD via an AHR-dependent and protein kinase-dependent non-genomic pathway that does not require AHR nuclear localization (Li et al 2010). On the other hand, AHR activation by TCDD can disrupt nuclear factor-ÎșB signaling and suppress acute phase response genes such as serum amyloid protein A3 (Saa3) via a mechanism that does not require binding of AHR to a DRE (Patel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous AHR agonists appear to have dual effects on inflammatory signaling. On the one hand, TCDD exposure can induce inflammatory responses as exemplified by: (a) the synergistic induction of IL-6 expression caused by interleukin-1ÎČ and TCDD co-treatment via an AHR-dependent and DRE-mediated mechanism (Hollingshead et al 2008); and (b) induction of Socs3 expression by TCDD via an AHR-dependent and protein kinase-dependent non-genomic pathway that does not require AHR nuclear localization (Li et al 2010). On the other hand, AHR activation by TCDD can disrupt nuclear factor-ÎșB signaling and suppress acute phase response genes such as serum amyloid protein A3 (Saa3) via a mechanism that does not require binding of AHR to a DRE (Patel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that, in both the human MCF-7 breast cancer cell line and the ECC1 endocervical cancer cell line, IL6 production is synergistically increased following concomitant exposure to an AHR ligand and pro-inflammatory IL1␀ (6). The low level of AHR activation needed to mediate this response, combined with the fact that increased IL6 protein secretion continued for 72 h after the initial dose of ligand, points to a potentially low threshold that cancer cells must pass before producing and releasing extensive amounts of a known pro-growth signal.…”
mentioning
confidence: 99%
“…Thus, it is important to assess potential toxicological interactions between components of a chemical mixture in exposed populations. As we noted above, pro-inflammatory molecules can significantly amplify the effects of AhR ligands (Hollingshead et al, 2008;UmannovĂĄ et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…We hypothesize that the mechanism by which TNF amplified the effects of AhR ligands was by inducing an over-expression of the AhR. In this context, Hollingshead et al (2008) showed that TCDD treatment in combination with IL-1 or phorbol 12-myristate 13-acetate (PMA) resulted in a marked synergistic induction of IL-6 levels over that seen without AhR activation in MCF-7 cells. Since TCDD induces IL-6 expression through the AhR pathway, those authors suggested this synergistic effect could be partly explained by an inflammation-induced increase in AhR expression.…”
Section: Discussionmentioning
confidence: 99%